Narratives of Italian Transatlantic (re)migration, 1897–1936 - Viola, Lorella (Frontiers in Sociology, 2023)
Remigration is typically envisioned as the final stage of the migration experience, a one-way movement from the host country to the country of origin. This article offers a novel, intimate view of historical return migration as a more complex and discursive process. The case study is Italian American migrants at the turn of the twentieth century, one of the groups which – according to historical statistics – was most actively engaged in Transatlantic remigration; more recent readings, however, show that many of these returnees eventually re-emigrated to the US. Using for the first time immigrant newspapers against the baseline of the Italian public discourse, the article analyzes Italian migrants’ own accounts of remigration as a way to access the more subjective dimension of migration. The integration of text mining and Critical Discourse Analysis will show that migrants were experiencing migration as a sense of identity crisis manifested through feelings of being misunderstood, rejected and unappreciated. These results indicate a less material reading of (re)migration, that is beyond economic reasons, and that for many individuals remigration was a bi-directional movement, only fully concluded when they were no longer experiencing a sense of identity crisis, be it in their homeland or the host society. The article will argue that this was the visible outward sign of a much more profound issue: the Italian Government’s view of (r)emigration –mainly through the lens of domestic economic advantage –deeply underestimated the complexity of migration as a social phenomenon and as a profoundly changing psychological experience. In the long run, this error of judgment deeply damaged Italy as many of those ritornati felt misunderstood and disillusioned and crossed the Atlantic again, this time never to return.